Mycotoxin Biodegradation by Bacillus Bacteria—A Review - Thanh Nguyen; Xiaojing Chen; Linlin Ma; Yunjiang Feng (Toxins)
Mycotoxins are toxic secondary metabolites produced by various types of fungi that are known to contaminate various food products; their presence in the food chain poses significant risks to human and animal health and leads to enormous economic losses in the food and feed industry worldwide. Ensuring food safety and quality by detoxifying mycotoxin is therefore of paramount importance. Several procedures to control fungal toxins have been extensively investigated, such as preventive measures, physical and chemical methods, and biological strategies. In recent years, microbial degradation of mycotoxins has attracted much attention due to its reliability, efficiency, and cost-effectiveness. Notably, bacterial species from the Bacillus genus have emerged as promising candidates for mycotoxin decontamination owing to their diverse metabolic capabilities and resilience in harsh environmental conditions. This review manuscript aims to provide a summary of recent studies on the biodegradation of fungal toxins by Bacillus bacteria, thereby illustrating their potential applications in the development of mycotoxin-degrading products.